2022
DOI: 10.1108/wje-02-2022-0067
|View full text |Cite
|
Sign up to set email alerts
|

An improved parallel regenerative braking system for small battery electric vehicle

Abstract: Purpose The purpose of this paper is to design an improved parallel regenerative braking system (IPRBS) for electric vehicles (EVs) that increases energy recovery with a constant brake pedal feel (BPF). Design/methodology/approach The conventional hydro-mechanical braking system is redesigned by incorporating a reversing linear solenoid (RLS) and allowed to work in parallel with a regenerative brake. A braking algorithm is proposed, and correspondingly, a control system is designed for the IPRBS for its prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Jiang et al [71] reported that their energy recovery efficiency reached 55%. In the NEDC, Jiang et al [71] achieved an energy recovery efficiency of 55.3%, followed by Salari et al [80], Wager et al [81], Xiao et al [86], Mondal et al [84], Yin et al [70], and Xu et al [92]. Although our energy recovery efficiency is not as high as that of Jiang et al [71], it is better than others.…”
Section: Comparison Of Energy Recovery Performancementioning
confidence: 49%
“…Jiang et al [71] reported that their energy recovery efficiency reached 55%. In the NEDC, Jiang et al [71] achieved an energy recovery efficiency of 55.3%, followed by Salari et al [80], Wager et al [81], Xiao et al [86], Mondal et al [84], Yin et al [70], and Xu et al [92]. Although our energy recovery efficiency is not as high as that of Jiang et al [71], it is better than others.…”
Section: Comparison Of Energy Recovery Performancementioning
confidence: 49%
“…Instead, they can be used for charging EV batteries during the barking process [5], [6]. For instance, the kinetic energy wasted in the form of heat during the vehicle braking can be recovered by integrating RBS in EVs or by using hybrid braking systems [1], [7]- [9]. These braking systems are used to recover a portion of the wasted kinetic energy during braking vehicles in motion.…”
Section: Introductionmentioning
confidence: 99%
“…It was mentioned that, integrating RBS in buses and trains can reduce fuel consumption by about 30% and increase energy efficiency to 30% [4], [8], [10], [11]. To ensure the efficiency of the energy recovery process some parameters must be considered such as the type of used motor, the applied braking force and EV batteries, different road surfaces coefficients, driver intentions, state of charge of the battery, drive distance, motor braking torque and braking forces distribution on the wheels [2], [9], [12].…”
Section: Introductionmentioning
confidence: 99%